Supper from your terrace - Khapte, P S; Kumar, PRADEEP; Singh, Akath; Kumar, Praveen (Indian Horticulture, 2019)
In present scenario of growing health concern, soil and water pollution, and heavy load of pesticides, availability of safe, nutritious and quality food is limited. Terrace vegetable gardening is an ideal choice in which vegetables are grown in environmental friendly way in ones surrounding so as to enjoy them in aesthetic way, adding value to the life. It is high time to start terrace vegetable gardening in urban areas for leading quality and healthy life linked to urban agriculture. This besides providing quality fresh product from the terrace, provides aesthetic value, alternative to exercise and above all it contributes in reducing city waste as it offers the recycling of the kitchen wastes by composting to convert them in useful manure to partly sustain own terrace garden. The rain water harvesting structures could also be linked to the rooftop gardening. There is need to intensify education and training programs for city dwellers on sustainable terrace vegetable gardening practices.